The Influence of Emotional Intelligence, Job Promotion, Work Environment, Work Discipline on the Loyalty of Human Resources and Development Board Employees in Bintan Regency - Didi Kurniadi; Faisal hus; Putri Rahmawati; Verlina Y Kawangung (IAIC Publishing, 2021)
This study uses a causal model survey method using path analysis techniques. This study aims to confirm the theoretical model with empirical data, the study population is employees in Human Resources and Development Board Bintan Regency, which consists of civil servants with a sample of 39 members of civil servants. Data collecting technical using variable measurements using a questionnaire instrument, this instrument was developed based on theoretical studies. Data analysis uses descriptive statistics and statistical analysis. Statistical tests are used to test the significance of path coefficients using Partial Least Square (PLS) which is a Multivariate Analysis in the second generation using structural equation modeling (SEM). PLS can be used for a small number of samples and does not require the assumption that data distribution must be normal or not.Tthe relationship between variables formulated in the formulation of a problem as many as 7 pieces obtained significant results.